Effect of some genetic and non-genetic factors on productive and reproductive traits of Egyptian buffaloes - Ramadan, Sherif Ibrahim (Journal of Advanced Veterinary and Animal Research, 2018)
Objective: The objectives of our study were to estimate the effect of some non-genetic factors on production and reproduction traits of Egyptian buffaloes and to estimate the breeding values for these traits. Materials and Methods: Data from 965 lactation records of 305 Egyptian buffalo cows mated by 73 sires that were raised at Mahallet Mousa Experimental farms of Animal Production Research Institute were collected. Dairy records covered the period from 2001 to 2015. The data were arranged and statistically analyzed using SAS version 9.1.3 to study the effect of non-genetic factors and the MTDFREMAL program was included in estimating the expected breeding values. Results: Our results showed that buffalo cows that calved in winter season recorded the highest and significant total milk yield (TMY) and daily milk yield (DMY) traits and the best reproductive performance was indicated by the lower number of services per conception and the shortest calving interval (CI) period. Moreover, age at first calving and dry period (DP) showed a highly significant effect on the TMY and DMY. A significant effect for the level of milk production on days open (DO) period was recorded in our study. The range of sires EBV was 540 kg, 295.2 days, 113.9 days, 2.8 months, and 71.1 days for TMY, LL, DO, CI, and DP, respectively. Conclusion: Buffalo’s breeders must consider the season of calving, parity, and DP in management program because they greatly affect the farm productivity and profitability and they must select animals with higher breeding values to be the parent of the next generation. http://doi.org/10.5455/javar.2018.e287